The emerging molecular biology toolbox for the study of long noncoding RNA biology. (October 2017) - Fok, Ezio T; Scholefield, Janine; Fanucchi, Stephanie; Mhlanga, Musa M
Long noncoding RNAs (lncRNAs) have been implicated in many biological processes. However, due to the unique nature of lncRNAs and the consequential difficulties associated with their characterization, there is a growing disparity between the rate at which lncRNAs are being discovered and the assignment of biological function to these transcripts. Here we present a molecular biology toolbox equipped to help dissect aspects of lncRNA biology and reveal functionality. We outline an approach that begins with a broad survey of genome-wide, high-throughput datasets to identify potential lncRNA candidates and then narrow the focus on specific methods that are well suited to interrogate the transcripts of interest more closely. This involves the use of imaging-based strategies to validate these candidates and observe the behaviors of these transcripts at single molecule resolution in individual cells. We also describe the use of gene editing tools and interactome capture techniques to interrogate functionality and infer mechanism, respectively. With the emergence of lncRNAs as important molecules in healthy and diseased cellular function, it remains crucial to deepen our understanding of their biology.